Increased temperatures negatively affect Juniperus communis seeds: evidence from transplant experiments along a latitudinal gradient. (3rd November 2015) - Gruwez, R.; De Frenne, P.; Vander Mijnsbrugge, K.; Vangansbeke, P.; Verheyen, K.
Abstract: With a distribution range that covers most of the Northern hemisphere, common juniper ( Juniperus communis ) has one of the largest ranges of all vascular plant species. In several regions in Europe, however, populations are decreasing in size and number due to failing recruitment. One of the main causes for this failure is low seed viability. Observational evidence suggests that this is partly induced by climate warming, but our mechanistic understanding of this effect remains incomplete. Here, we experimentally assess the influence of temperature on two key developmental phases during sexual reproduction, i.e . gametogenesis and fertilisation (seed phase two, SP2) and embryo development (seed phase three, SP3). Along a latitudinal gradient from southern France to central Sweden, we installed a transplant experiment with shrubs originating from Belgium, a region with unusually low juniper seed viability. Seeds of both seed phases were sampled during three consecutive years, and seed viability assessed. Warming temperatures negatively affected the seed viability of both SP2 and SP3 seeds along the latitudinal gradient. Interestingly, the effect on embryo development (SP3) only occurred in the third year, i.e . when the gametogenesis and fertilisation also took place in warmer conditions. We found strong indications that this negative influence mostly acts via disrupting growth of the pollen tube, the development of the female gametophyte and fertilisation (SP2). This, in turn, can lead to failing embryo development, for example, due to nutritional problems. Our results confirm that climate warming can negatively affect seed viability of juniper.